A new erbium doped fiber amplifier - Ali, Sellami; Al-Khateeb, Khalid A. Saeed; Bouzid, Billoui (Asian Network for Scientific Information, 2009)
In this study, a new configuration of an Erbium Doped Fiber Amplifier (EDFA’s) is proposed. Double-pass amplification in a dual-stage using a fiber loop-back is incorporated with a Tunable band pass filter. Spontaneous emission is filtered-out in the mid-section to ensure efficient amplification of the signal as it propagates along the fiber. High gain of 61 dB is achieved for -50 dBm signal power at 1550 nm. The two stages were pumped by laser diodes operating at 980 nm with 10 mW and 220 mW, respectively.